Chapter 11 The power of apricot - Murzakulova, Asel (Taylor & Francis, 2023)
The apricot has a strong economic value in disputed areas along the Kyrgyzstan-Tajikistan border. It is also an important asset for migrant workers investments. This paper argues that tree's life cycle produces power relations, bonding communities in times of conflict, but also increasing vulnerability and tensions over water supply. The research shows how the apricot tree life cycle can govern the mobility choices of owners, and how recognition of its common value can give rise to cross-border acts of solidarity aimed at preserving the trees.